Comparison of nitrite production in chicken peritoneal macrophages after in-vitro infection with some Salmonella typhimurium poultry isolates - BHATTACHARYA, ASIS; SINGH, V P (The Indian Journal of Animal Sciences, 2014)
Nitrite is an important molecule of oxygen dependent pathway of intracellular killing mechanism of macrophages. Four Indian poultry isolates of Salmonella typhimurium (E 1841, E 2336, E 2385 and E 2187) and 1 European poultry strain of S. typhimurium (F 98) were tested for in-vitro induction of nitrite production in residential and elicited chicken peritoneal macrophages (CPM). Most of the isolates evoked production of higher amount of nitrite by inflammatory CPM than that of resident CPM after 48 hr of incubation postÂ·infection. F 98 strain infection resulted into higher nitrite production than Indian field S. typhimurium isolates in both resident and inflammatory macrophages.